KEANEKARAGAMAN JENIS DAN PEMANFAATAN SUMBERDAYA OLEH KELELAWAR SUB ORDO MEGACHIROPTERA DI TAMAN WISATA ALAM GUNUNG MEJA MANOKWARI, PAPUA BARAT - Bumbut, Petrus Izak; Kartono, Agus Priyono; Maryanto, Ibnu (Perhimpunan Biologi Indonesia, 2016)
Bats utilizing resources together will differ morphologically, ecologically, and behaviorally. This study aimed to measurespecies diversity and to investigate resource use by Megachiropteran bats. Data were analyzed using Principal ComponentAnalysis (PCA), Canonical Correspondence Analysis (CCA), Correspondence Analysis (CA), euclidean distance, chisquare, Anova, and niche overlap index. The result showed seven bat species were captured in three habitat types. Plant asfood identified from pollen comprised 55 species from 29 families and 11 types of corolla. Dobsonia magna and Rousettusamplexicaudatus preferred mixed fruit plantation, whilst other bat species tended to choose primary forest. Dobsonia minortended to have high niche overlap against Macroglossus minimus and Nyctemene aello. According to similarity of foodresource niche, Dobsonia magna, Dobsonia minor, and Macroglossus minimus tended to closely associate, in contrast,Rousettus amplexicaudatus, Nyctemene albiventer, Nyctemene aello, and Syconicteris australis were groupedcorrespondingly. Niche overlap index of food resource among bat species were overall less than 50%. This indicated thatthere was no interspecies competition to food resource. Coronoid process height (CPH), maximum zygomatic breadth(MZB), and condyle to canine bite point (CC) were craniodental morphology variables which did not describe certaincorolla types.Keywords: species diversity, resource use, niche overlap, Megachiropteran, Gunung Meja